Cervus and cucumis peptides combined umbilical cord mesenchymal stem cells therapy for rheumatoid arthritis. Issue 28 (10th July 2020) - Qi, Tao; Gao, Hongxiang; Dang, Yazheng; Huang, Shigao; Peng, Minfei
Abstract : Abstract: Cervus and cucumis peptides (Lugua polypeptides, LG) are traditional Chinese medicine, which are active components of polypeptide extracted from Sika deer bone and melon seed, and they contain bone induced polypeptide biological factors. Umbilical cord mesenchymal stem cell, (UC-MSC) have tissue repair multiple effects, anti-inflammatory, and immune regulation function, which become a very promising start in rheumatoid arthritis (RA) treatment. Hence, LG combined UC-MSC can significantly enhance the UC-MSC treatment of rheumatoid arthritis (RA). To explore the clinical curative effect and therapeutic mechanism of LG combined UC-MSC for treating RA. 119 patients were divided into control and treatment groups, and both groups were treated with methotrexate tablets, leflunomide, and UC-MSC. But, LG were added to the treatment group. In vitro, the effects of LG on UC-MSC cell secretion of anti-inflammatory factors were also performed. The Health Assessment Questionnaire; the 28 joint disease activity score; C reactive protein; the erythrocyte sedimentation rate; rheumatoid factor; and anti-cyclic citrullinated peptide antibody were significantly reduced in treatment group 1 year after treatment ( P < .05). In vitro, compared with the control group, the number of hepatocyte growth factor (HGF), the secretion of prostaglandin E2 (PGE2) and tumor necrosis factor-inducible gene 6 protein (TSG6) increased significantly ( P < .05). LG combined UC-MSCs can significantly improve the curative effect of RA patients, while LG may reduce inflammatory cytokines, regulate immunity, improve microcirculation, and are conducive to UC-MSCs migration and the repair of damaged tissue.